Examining the relationship between sport, physical activity and “Green Attitudes” among students in different university programmes - Moravecz, Marianna; Centeri-Baraksó, Eszter; Sikolya-Kertész, Kinga; Kovács, Karolina Eszter (Frontiers in Sports and Active Living, 2025)
The United Nations 2030 Agenda framework highlights the role of sport in sustainable development in areas such as healthy lifestyles, well-being, quality education, gender equality and peaceful societies. Thus, the goals of Agenda 2030 are consistent with the goals of the Olympics. The IOC's holistic approach to the 2024 Paris Olympic Games went beyond environmental factors to include the sustainability of athletes' mental well-being. The main objective of our research is to map the role of green attitudes and sport in the sustainable habits of Generation Z university students aged 18–29 in the disadvantaged Northern Great Plain region. We examined three distinct fields of study: sports (N = 170), education (excluding physical education) (N = 176) and technical-agricultural (N = 170). The total number of respondents was 509 (N = 509). To collect data, an online questionnaire was used, which was completed voluntarily and anonymously. We sent the link to the questionnaire to students at the University of Nyíregyháza, thus ensuring that we only received responses from the region we wanted to study. The questionnaire was designed to collect information on six dimensions. The data were analysed using SPSS Statistics 25.0, in which we used Chi-square, Kruskal–Wallis test, Mann–Whitney test, and exploratory factor analysis. Concerning our first three hypotheses, based on the negative outlook of Generation Z. These young people face a declining social role and unfavorable economic conditions, which affect their general worldview, value system, and vision for the future. We point to the phenomenon of “neutral spillover”, which is an area where sport does not play a role in students' green environmental mindset. This is consistent with the previous findings, which indicate the uncertain living conditions of today's young university students. A novel aspect of our study is the Olympic factor developed in connection with the 2024 Paris Olympics and the “green” and “social” factors obtained within it. We use these to highlight the positive spillover effect of global sporting events, which influences university students' attitudes towards sustainability about mental well-being, providing an opportunity for sport to become a tool for sustainability education, especially among younger generations. Physical and mental well-being are crucial in the lives of the Generation Z surveyed, which reinforces the relevance of our topic regardless of field of study, gender and social status. As this generation has been socialised in the media world, the internet may also play a central role in terms of involvement in eco-conscious sporting events. This age group is referred to as the world's first global generation, the “Instant Online” generation, for whom multitasking is a defining lifestyle. Environmental challenges are becoming increasingly urgent, so it is essential to educate younger generations about the environment, even through international sporting events promoted by the media. Further research directions could include extending the survey to universities in different regions of the country and repeating the questionnaire longitudinally for comparison purposes.